(untitled) (Revista Contexto & Saúde, 2026)
Objective: To evaluate the Work Ability Index in hospital workers in the context of the COVID-19 pandemic. Methodology: This cross-sectional, quantitative study was conducted with 79 workers at a private hospital in a town in the state of Goiás. The Work Ability Index was used for data collection. Data were analyzed descriptively and inferentially, with a significance level of 5%. Results: Most professionals were female (79.74%); 49.35% were married or living with partners; 31.64% had graduate degrees. The highest labor activity rate (60.74%) was among professionals with direct patient contact; 62.02% worked the day shift, and 79.94% were direct hospital workers. As for work ability, the general categorization showed that 50.63% of hospital workers had good work ability. In the analysis of labor factors, significance was found (p = 0.003) using Fisher’s test for work requirements, both physical and mental. The variable “being from the health area” showed a greater predisposition to a reduction in the Work Ability Index. Conclusion: The analyses show evidence that workers are becoming ill and, consequently, their work ability is declining. These factors can directly affect the health and quality of life of workers in hospital environments.